2018
DOI: 10.18203/2320-6012.ijrms20183636
|View full text |Cite
|
Sign up to set email alerts
|

A study of thyroid function in premenopausal and postmenopausal women of Dibrugarh town, Assam, India

Abstract: Background: Ageing process can cause some changes in body system controlling mechanism. Consequently thyroid hormone levels may show variations reflected by TSH level in elderly people, more so in females.Methods: Serum TSH level were measured in 304 apparently healthy females of Dibrugarh town, Assam. Unbound T3 and T4 were measured if TSH level was abnormal. TSH levels were compared among different age groups.Results: The prevalence of hypothyroidism was found to be 8.2% in premenopausal and 12.7% in postmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…In a study by Bordoloi et al, the correlation was not significant in both the groups. 8 Comparison of thyroid status had shown higher hypo and hyperthyroid cases in post-menopausal women when compared to pre-menopausal women which was statistically not significant. Garg et al observed that, about 21% of the post-menopausal women had subclinical hypothyroidism.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In a study by Bordoloi et al, the correlation was not significant in both the groups. 8 Comparison of thyroid status had shown higher hypo and hyperthyroid cases in post-menopausal women when compared to pre-menopausal women which was statistically not significant. Garg et al observed that, about 21% of the post-menopausal women had subclinical hypothyroidism.…”
Section: Discussionmentioning
confidence: 89%
“…A study by Bordoloi et al had shown that, the post-menopausal women had significantly higher TSH levels than premenopausal women. 8 A study by Kolanu et al had reported that, the mean TSH and T 4 were higher and T 3 was lower in post-menopausal women than the pre-menopausal women. 1 Patwa et al also observed similar results.…”
Section: Discussionmentioning
confidence: 97%
“…252) before the data collection. Females with history of menopause was ≥49 years and wherever clinical data was not available, we considered this age cut off as post menopause based on a recent study 8 done in Nepal wherein the age for menopause was given to be 48.7 years.…”
Section: Methodsmentioning
confidence: 99%
“… 1 , 2 Many authors have reviewed that the thyroid dysfunction prevalence among the elderly people is rising, especially in the postmenopausal women 3 - 6 A study from Nepal 7 have shown that females >40 years were more prone to develop thyroid dysfunction. In India 8 the prevalence of thyroid disorders is more common in postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, oestrogen, the primary female sex hormone suppresses IFNγ [145]. In menopause oestrogen levels decrease, as oestrogen decrease IFNγ expression increases, which elucidates why the incidence of hypothyroidism increases significantly in postmenopausal women [188,189,190,191]. However, it is important to note that serum F levels have also been shown to increase significantly in women post menopause [192,193,194].…”
Section: Molecular Mechanisms Of Fluoride Inhibition Of Iodine Hommentioning
confidence: 99%